Novel approaches and practices to sustainable agriculture - Seid Hussen Muhie (Journal of Agriculture and Food Research, 2022)
The world population is increasing in a disquieting rate while the quantity of food to gratify this snowballing human population is an annoyance to agrarian scientists and policymakers around the globe. Today's population is snatching natural resources from the future which can endanger the future generation's right to have nutritious food and clean air. The causes for this challenge can be enumerated and listed out, but singled out as lack of and/or poor implementation of novel approaches and practices for sustainable agriculture. Some of the novel approaches are but not limited to climate smart agriculture (CSA), organic farming, biodynamic agriculture, sustainable intensification and regenerative agriculture; and novel practices as integrated farming system (IFS), precision agriculture, integrated nutrient management (INM) and integrated pest management (IPM). The adoption of these approaches and practices has been proven to safeguard agricultural sustainability.